Instrument intercomparison in the high-energy field at the CERN-EU reference field (CERF) facility and comparison with the 2017 FLUKA simulations. (October 2018) - Dinar, N.; Pozzi, F.; Silari, M.; Puzo, P.; Chiriotti, S.; De Saint-Hubert, M.; Vanhavere, F.; Van Hoey, O.; Orchard, G.M.; Waker, A.J.
Abstract: This paper discusses an instrument intercomparison performed in the high-energy field at the CERF facility at CERN between 2015 and 2017 (October 2015, May 2016, November 2016 and June 2017). Measurements were performed in several reference exposure locations with the CERN extended-range Bonner Sphere Spectrometer (BSS), a Berthold LB4611, the LINUS rem counter from CERN, the LUPIN rem counter from ELSE Nuclear, the FHT 762 Wide Energy Neutron Detection Instrument (WENDI-II) from Thermo Scientific, the LUDLUM MODEL 42–41 PRESCILA NEUTRON PROBE and two models of Tissue-equivalent proportional counters (TEPCs) from Far West Technologies. All results are compared with the latest FLUKA reference values from simulations performed in 2017. Highlights: The BSS, WENDI II, LINUS and LUPIN agree amongst them and with the FLUKA simulations within one sigma of uncertainty. The LB6411 underestimates up to 35% as compared to FLUKA and the extended rem counters. The PRESCILA overestimates the high-energy component and underestimate the evaporation part. Therefore, the PRESCILA overestimates the H*(10) on the CT and underestimates it on the IT. Concerning the two TEPC, they agree within their range of uncertainty for all positions. The agreement with FLUKA is satisfactory on the CT/CS but the TEPCs show underestimation on the IT.